G107(P) Portal vein obstruction: The challenge of timely diagnosis. (24th May 2017) - Belsha, D; Davison, S; Hodges, S; Rajwal, S; McClean, P
Abstract : Background: Portal vein obstruction (PVO) due to thrombosis with cavernoma formation is a major cause of portal hypertension. Significant morbidity occurs due to oesophageal variceal bleeding. Early diagnosis provides an opportunity for prophylactic intervention. Aim: evaluate the spectrum of clinical presentation of PVO, and identify opportunities for early diagnosis. Methods: Children born after 1990 with final diagnosis of PVO referred to single centre 2000 – 2015 were studied. Data collected retrospectively: initial symptoms, signs and investigations, incidence of gastrointestinal (GI) bleeding and time to diagnosis. Results: Fifty-six children identified, one excluded (insufficient data). Age at presentation 3y 10m (1 m 13y 8 m), 26 male. Risk factors identified in 28/55 (51%): umbilical vein instrumentation (12), congenital heart disease (10) other congenital anomalies (6). Four patterns of presentation identified: (a) incidental finding of PVO on US (n=9); (b) neonatal jaundice +/ascites with US diagnosis of PVO (n=4); (c) upper GI bleed (n=22) and (d) 'haematological presentation' with splenomegaly and/or symptoms/signs of hypersplenism (n=20). Of 22 presenting with GI bleeding (mean age 3y 6m, 6m–10y6m) 15 had diagnosis established during admission. Seven were discharged without PVO identified: all readmitted after median 1m (7d – 18m) with further bleeding, after which diagnosis established. Three with GI bleed at presentation were initially referred to haematology for investigation of thrombocytopenia, two undergoing bone marrow (BM) assessment. Of 20 children (mean age 5y 2m, 17 m-13 y) with 'haematological presentation', 13 (65%) were referred to haematology (11) or immunology (2). BM assessment performed in 9/20 (45%) was normal. Only 9/20 (45%) in this group had diagnosis of PVO established within 2w of presentation. In 11 median interval to diagnosis was 10 m (2m – 6y). Of these, 10 had a significant GI bleed during the interval to diagnosis. Conclusion: PVO has wide spectrum of presentation. Associated risk factors in 51% may aid diagnosis. Diagnosis was delayed in 18/42 (43%), most frequently in those with 'haematological' presentation (55%) but also in those with GI bleed (32%). Carefully focussed imaging by US with Doppler and/or other radiological modalities should be undertaken in a child with history, symptoms or signs compatible with PVO.